2022
DOI: 10.3390/s22239178
|View full text |Cite
|
Sign up to set email alerts
|

Characterisation and Quenching Correction for an Al2O3:C Optical Fibre Real Time System in Therapeutic Proton, Helium, and Carbon-Charged Beams

Abstract: Real time radioluminescence fibre-based detectors were investigated for application in proton, helium, and carbon therapy dosimetry. The Al2O3:C probes are made of one single crystal (1 mm) and two droplets of micro powder in two sizes (38 μm and 4 μm) mixed with a water-equivalent binder. The fibres were irradiated behind different thicknesses of solid slabs, and the Bragg curves presented a quenching effect attributed to the nonlinear response of the radioluminescence (RL) signal as a function of linear ener… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 70 publications
0
2
0
Order By: Relevance
“…However, these detectors may be particularly complicated to characterize and use in carbon beams. Data from prior OSLD experiments have shown a detector response that is dependent on linear energy transfer (LET) (Yasuda and Kobayashi 2001, Sawakuchi et al 2008, Reft 2009, de Freitas Nascimento et al 2022. Additionally, a more recent study by Parisi et al demonstrated particle type dependence in Al 2 O 3 :C response (Parisi et al 2022).…”
Section: Introductionmentioning
confidence: 99%
“…However, these detectors may be particularly complicated to characterize and use in carbon beams. Data from prior OSLD experiments have shown a detector response that is dependent on linear energy transfer (LET) (Yasuda and Kobayashi 2001, Sawakuchi et al 2008, Reft 2009, de Freitas Nascimento et al 2022. Additionally, a more recent study by Parisi et al demonstrated particle type dependence in Al 2 O 3 :C response (Parisi et al 2022).…”
Section: Introductionmentioning
confidence: 99%
“…Their method does not measure LET directly using its physics definition instead measures the ratio of ultraviolet to blue emission intensities as a surrogate of LET, and uses MC simulations to establish a relationship between the surrogate parameter and LET. A few other methods are available for proton LET measurement, [10][11][12][13][14][15] but all similarly employ surrogates and require MC simulations to calibrate the surrogates and LETs.Lineal energy,the energy imparted at each event in a volume of interest divided by the mean chord length in that volume, 16 is another surrogate of LET and can be measured with microdosimeters. 17,18 MC has been used to simulate the energy-dependent mean chord length in the detector sensitive volume.…”
Section: Introductionmentioning
confidence: 99%